Improving care home life for people with Parkinson's. (2nd June 2019) - Oates, Lloyd; Hand, Annette; Dismore, Lorelle; Gray, William; Walker, Richard
Abstract : Lloyd Oates, Annette Hand, Lorelle Dismore, William Gray and Richard Walker discuss a study they carried out into the wellbeing of people with Parkinson's disease in care homes and make a number of recommendations based on thematic analysis of the data.